SIKAP PROFESIONALISME DAN KODE ETIK AUDITOR INTERNAL CECYLIA DEWI SINNIARTO WONGSO - DEWI SINNIARTO WONGSO, CECYLIA (: 2303-1719)
Internal auditors conducting an impartial assessment of an organization to conduct audits in a required accounting firms, financial audits and other operations that are fundamental to aid management. Profession of internal auditors should have high moral commitment embodied in the form of a code of ethics rules. Professional internal auditors in performing the tasks always held code of ethics. The results of the discussion can be made several conclusions as follows professional internal auditors influenced the ability or skills they have. Increasingly have more skills will be increased and vice versa. Professionalism as an attitude and behavior in performing certain professions. Someone who has the professional expertise and technical skills should have the seriousness and precision work, the pursuit of the satisfaction of others, courage to risk, perseverance and determination, integrity, consistency and unity of thought, word, and deed. A professional is always based on the knowledge gained employment.